Preaching in Early Medieval Frankish Monasteries: The Auxerre Homiliary Assigned to Haimo - Galle, Christoph (The Downside review, 2019)
The goals of my study were first to show the characteristic features of the homiliary assigned to Haimo of Auxerre compared to four other Carolingian sermon collections of the 8th and 9th centuries and second to explain why its audience should be found within the Frankish monasteries.